2011
DOI: 10.1149/1.3530794
|View full text |Cite
|
Sign up to set email alerts
|

Water Transport Across a Polymer Electrolyte Membrane under Thermal Gradients

Abstract: A fundamental experimental and numerical study of the water transport across a perfluorosulfonic acid membrane under a temperature gradient is presented. The water transport phenomenon was experimentally investigated through water flux measurement and neutron radiography. The experimental observations found that water is transported in the direction from the high temperature side to the low temperature side, when both sides of the membrane are sufficiently humidified, and suggest that the transport mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Their study found the importance of heat and water management inside the cell under high current density operations. Fu et al (10) also supported their experimental results with a one-dimensional, two-phase, non-isothermal model. Their numerical analysis revealed the capabilities and limitations of the numerical prediction of the through-plane water distribution inside the MEA.…”
Section: Introductionmentioning
confidence: 70%
“…Their study found the importance of heat and water management inside the cell under high current density operations. Fu et al (10) also supported their experimental results with a one-dimensional, two-phase, non-isothermal model. Their numerical analysis revealed the capabilities and limitations of the numerical prediction of the through-plane water distribution inside the MEA.…”
Section: Introductionmentioning
confidence: 70%
“…50% to 70% of the energy exiting the cell as heat, recent works have therefore examined the impact of the temperature field on water transport in the fuel cells MEA [1][2][3][4][5][6][7][8][9][10]. In 2002, Djilali and Lu [1] focused on the modeling of non-isothermal and non-isobaric effects (including Knudsen diffusion and Soret effects).…”
Section: Nomenclaturementioning
confidence: 99%
“…Eikerling [4] also showed that at a current density of 1 A.cm -2 , the evaporation rate at the electrode is sufficient to remove all water produced at the cathode in vapor phase. To visualize this phenomenon, Hickner et al [5,6], Kim and Mench [7,8] and Fu et al [9], used neutron radiography highlighted the importance of evaporation at high current densities. The temperature influence on the water is significant, on its state but also on its transport.…”
Section: Nomenclaturementioning
confidence: 99%
“…laboratory X-rays) cannot be implemented. Neutron imaging with thermal and cold neutrons provides unique contrast and is often used to study internal structure and the presence of defects in various metal samples (Kockelmann et al, 2007;Bilheux et al, 2009;Kardjilov et al, 2012;Lehmann et al, 2009), as well as the distribution of hydrogen-containing substances within metals (Grosse et al, 2013;Griesche et al, 2015;Tremsin, Morgano et al, 2015), water in proton exchange membrane fuel cells (Fu et al, 2011;Stahl et al, 2015), coolant in heat pipes (Cimbala et al, 2004), diesel in fuel injectors (Lehmann et al, 2015) and many others. At the same time, neutron diffraction is widely used for studies of crystallographic properties as the wavelengths of thermal and cold neutrons are comparable to lattice parameters (several ISSN 1600-5767 å ngströ ms) (Vogel, 2000;Santisteban et al, 2001Santisteban et al, , 2002Hutchings et al, 2005).…”
Section: Introductionmentioning
confidence: 99%